Moral Poems and Verses for Schools and Colleges - Omoniyi, Funmilayo (Evans Brothers (Nigeria Publishers) Ltd, 2001)
This book is aimed at inculcating the love of reading in our youth and drawing their attention to the moral decadence pervading the society, thereby giving them food for thought in this regards$1! =s
Keywords: Poems